Mangroves of the Nicoya Peninsula, Costa Rica - Bravo, Juan (2005)
Mangrove swamp ecosystems are spread along the Costa Rican Pacific Coast from Puerto Soley until the estuary of Coto Colorado River. In the Nicoya Peninsula, the most important area is formed by the mangrove swamps in the Tempisque River estuary system and a sector in the Nicoya Gulf. They extend over a big surface along the riverbanks in the aforementioned estuary, from Bolsón River until the Cabo Blanco estuary, in the border of the inner sector in the gulf. It includes a large portion ranging in width, from a few meters up to six kilometers, like the mangrove swamps in the Letras estuary. The direct and indirect impacts on such waterlogged areas affect in a negative way on this estuarial ecosystem, pollution by agrichemical products is a very important shocking effect presented in a short term. Likewise, the transformation in the land use in inner areas has influence by adding sediments and chemical residues. In addition, the development in the growing tourist activity in the open coastland area in the peninsula, based in a disorderly use in the marine coastal zone, has made some damage too. It must be added to these impacts, the effect in the climatic changes over these areas.